Declaration of Principles and Plan of Action on Tourism, Trade and Transportation ([Association of Caribbean States] [Port of Spain]TT, 1995)
Sets out the objectives of according priority to tourism, trade and transportation in the Association's concerted actions to promote cooperation, thus advancing the development of its peoples and laying the foundation for progress in other areas of interest. Presents a Plan of Action.
DC